Proving content validity of android-based higher order thinking skill assessment for science and mathematics preservice teacher - Susantini, Endang; Sari, Yurizka Melia; Asteria, Prima Vidya; Marzuqi, Muhammad Ilyas (Intelektual Pustaka Media Utama, 2025)
Assessing preservice' higher order thinking skills (HOTS) in science and mathematics is essential. Teachers' HOTS ability is closely related to their ability to create HOTS-type science and mathematics problems. Among various types of HOTS, one is Bloomian HOTS. To facilitate the preservice teacher to create problems in those subjects, an Android app called EduAssess was developed as a Bloomian HOTS test for junior high school preservice teachers. This study aims to validate the problems in the EduAssess app through content validity. Content validity was analyzed using Aiken's V formula and expanded Gregory formula. EduAssess comprised three test sets for science and mathematics, each comprising 9 items. The instrument validated by three experts in each subject. The study results demonstrate that EduAssess, for both mathematics and science, has achieved content validity. Expert judgments confirmed the validity of EduAssess items, with Aiken's V index ranging from 0.67 to 1.00, meanwhile expanded Gregory index ranging from 0.78-1.00. The results showed that EduAssess includes analysis, evaluation, and creation. The findings highlight that the application instrument in facilitating pre-service teachers by measuring their ability to analyze, evaluate and create HOTS problems in science and mathematics subjects was proven valid and ready for data collection.